Endorsement of reporting guidelines and clinical trial registration across urological medical journals: a cross-sectional study - Alex Hagood; Joseph Case; Trevor Magee; Caleb Smith; Danya Nees; Griffin Hughes; Matt Vassar (PeerJ)
Introduction Over the years, funding for urologic diseases has witnessed a steady rise, reaching $587 million in 2020 from $541 million in 2018. In parallel, there has been a notable increase in the total number of urology journals from 2011 to 2018. This surge in research funding and journal publications calls for urologists to effectively navigate through a vast body of evidence to make the best evidence-based clinical decisions. Our primary objective was to assess the “instructions for authors” of these journals to determine the extent of endorsement of reporting guidelines for common study designs in medical research. Methods Top urology journals were identified using the 2021 Scopus CiteScore and confirmed via Google Scholar Metrics h5-index. In a masked, duplicate manner, two investigators retrieved data from the “instructions for authors” webpages of the included journals. For each journal investigated in our study, the following data were extracted: journal title, 5-year impact factor, email responses of journal editors, mention of the EQUATOR Network in the “instructions for authors,” mention of the ICMJE in the “instruction for authors,” geographical region of publication and statements about clinical trial registration. Results Of the 92 urology journals examined, only one-third (32/92) mentioned the EQUATOR network in their “instructions for authors.” A total of 17 journals (17/92, 18.5%) did not mention a single reporting guideline. The most endorsed guideline was CONSORT at 67.4% (62/92). Clinical trial registration was not mentioned by 28 (30%), recommended by 27 (29%), and required by 37 journals (40%). Conclusion Our findings indicate that urology journals inconsistently endorse reporting guidelines and clinical trial registration. Based on these results, we propose that urology journals adopt a standardized approach, incorporating explicit requirements for reporting guidelines such as those listed on the EQUATOR Network and clinical trial registration for all relevant study designs. Specifically, journals should consider clearly stating mandatory or recommended guidelines for clinical trials, observational studies, and systematic reviews, among others. Future efforts should focus on evaluating the implementation of these policies and identifying barriers that hinder their adoption.